Who Benefits from Gamification? The Role of Web-Based Board Games in Fostering Pancasila Values among Elementary Learners - Ida Bagus Made Wisnu Parta Wisnu; Ida Ayu Putu Purnami; Ida Ayu Kartika Maharani (Jurnal Ilmiah Sekolah Dasar, 2025)
Strengthening Pancasila values in elementary school students requires innovative learning approaches that enhance motivation, engagement, and meaningful character development. However, character education practices remain largely conventional and lack contextual learning experiences for students. This study aims to analyze and examine the effectiveness of web-based digital board games as a gamification medium for internalizing Pancasila values among elementary school students. The study employed a quantitative approach using a quasi-experimental design. The research subjects consisted of 162 elementary school students grouped according to learning achievement levels. Data were collected through pretests, posttests, and records of game achievement as instruments to measure learning outcomes and value internalization. Data analysis was conducted using statistical software, employing paired-samples t-tests to compare pre- and post-intervention results, Pearson correlation to examine the relationship between initial ability and final outcomes, and one-way ANOVA followed by Tukey HSD post hoc tests to identify differences in achievement across groups. The results indicate that web-based digital board games are effective in enhancing the internalization of Pancasila values, with the most optimal impact observed among students with moderate ability levels. These findings suggest that web-based gamification has significant potential to support character education. Practically, the results provide guidance for teachers to adapt gamification strategies based on students’ ability profiles in order to strengthen Pancasila education in elementary schools.